Methods of Controlling the Physical Loads of Players (Texas Journal of Multidisciplinary Studies, 2022)
In order to further develop mass and professional football in Uzbekistan, to strengthen its material and technical base, to train and educate a new generation of players, to increase the international prestige of football in our country, the president of the Republic personally and to the Makhkam of Ministers Sh.Great attention is being paid by Mirziyoyev, relevant decisions, decrees and laws are being developed and implemented in life, which is the basis for the development of sports